Association of C-262 polymorphism in catalase gene with Rheumatoid Arthritis - Tayyab, Yusra; Amir Rashid; Muhammad Javad Yousaf; Asifa Majeed; Muhammad Adnan Manzar (Journal of the Pakistan Medical Association, 2022)
Objectives: To evaluate the association of C-262 polymorphism in Catalase gene (CAT) with Rheumatoid Arthritis. Method: The comparative cross-sectional study was conducted at the Department of Biochemistry and Molecular Biology, Army Medical College, Rawalpindi, in collaboration with the Rheumatology Department, Pak Emirates Military Hospital, Rawalpindi, Pakistan, from January to December 2020, and comprised Deoxyribonucleic acid extraction of samples. Samples in group I belonged to diagnosed rheumatoid arthritis patients of either gender aged 30-60 years who were on disease-modifying anti-rheumatic drugs. Group II had an equal number of healthy controls. The promoter region of the CAT gene having the polymorphic segment was amplified through polymerase chain reaction, and its products were then subjected to restriction fragment length polymorphism for the analysis of polymorphic region of the CAT gene. Genotypic frequency equilibrium and the association of polymorphism with rheumatoid arthritis was checked. Also, association between fasting lipid profile and haemoglobin was assessed. Data was analysed using SPSSS 22. Results: Of the 60 samples, 30(50%) belonged to each of the two groups. The mean age was 44.90±10.50 years (range: 30-60 years). Overall, there were 34(56.7%) males and 26(43.3%) were females. Two alleles and three genotypes of the polymorphism was detected. The frequency of CC genotype was higher in group I 23(76.6%), but no association of any of the genotype of polymorphism was found significant (p 0.05). Haemoglobin and lipid profile levels were significantly different in the two groups (p 0.05). Conclusion: There was no significant association found between C-262 polymorphism in CAT gene and rheumatoid arthritis. Key Words: Rheumatoid arthritis, CAT gene, C-262T polymorphism, Restriction fragment length polymorphism.